Analisis SWOT Sebagai Dasar Perencanaan Pengadaan Cloud Storage Untuk Transformasi Digital Di PT Lokabyte Digital Innovations - Musantono, Agus Eko; Anam, Chairul; Susilo, Erdiyanto Luthfi; Juniartha, Rhegysa Alvyanthi (Sekolah Tinggi Ilmu Komputer PGRI Banyuwangi, 2025)
Digital transformation demands that companies implement data storage systems that are flexible, secure, and accessible from various locations. This study aims to design a cloud storage procurement strategy for PT Lokabyte Digital Innovations using a SWOT analysis approach. The method applied is descriptive qualitative, involving data collection through system observation, internal interviews, and literature review. The analysis reveals that the company has strengths in adaptability and team creativity, but faces weaknesses in unstandardized data storage infrastructure. There are opportunities in digitalization and remote work, although risks related to data security and third-party dependence persist. Based on these findings, three strategic alternatives are recommended: Google Drive (public cloud), NAS (private cloud), and a hybrid combination of both. These alternatives are presented equally, allowing the company to select based on its resources and growth trajectory. The study is expected to serve as a strategic reference in supporting digital transformation in emerging digital enterprises.